2013
DOI: 10.1099/ijs.0.051623-0
|View full text |Cite
|
Sign up to set email alerts
|

Micromonospora schwarzwaldensis sp. nov., a producer of telomycin, isolated from soil

Abstract: A Gram-stain-positive, spore-forming actinomycete strain (HKI0641 T ) was isolated from a soil sample collected in the Black Forest, Germany. During screening for antimicrobial natural products this bacterium was identified as a producer of the antibiotic telomycin. Morphological characteristics and chemotaxonomic data indicated that the strain belonged to the genus Micromonospora. The peptidoglycan of strain HKI0641T contained meso-diaminopimelic acid, and the fatty acid profile consisted predominantly of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In the 1960s, a first partial structure of telomycin containing a permutation of three amino acids was published. , Two nuclear magnetic resonance (NMR) based studies on telomycin in 1973 provided the correct structure of the complex molecule. , Telomycin ( 1 , Chart ) is a cyclic depsipeptide which is composed of 11 amino acids including five non-proteinogenic ones. It is composed of a nonapeptide lactone ring formed between the 4 Thr hydroxyl group and the C-terminal carboxyl group. Only a few reports on this compound were published after the structure of telomycin was elucidated, and to date, the mode of action (MoA) is still unclear. However, studies on a truncated analogue of telomycin lacking an aspartic acid and hydroxylation of cis -3-hydroxyl-proline called LL-AO341 β 1 revealed that specific inhibition of DNA, RNA, protein, lipid, or peptidoglycan synthesis by LL-AO341 β 1 could not be detected.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s, a first partial structure of telomycin containing a permutation of three amino acids was published. , Two nuclear magnetic resonance (NMR) based studies on telomycin in 1973 provided the correct structure of the complex molecule. , Telomycin ( 1 , Chart ) is a cyclic depsipeptide which is composed of 11 amino acids including five non-proteinogenic ones. It is composed of a nonapeptide lactone ring formed between the 4 Thr hydroxyl group and the C-terminal carboxyl group. Only a few reports on this compound were published after the structure of telomycin was elucidated, and to date, the mode of action (MoA) is still unclear. However, studies on a truncated analogue of telomycin lacking an aspartic acid and hydroxylation of cis -3-hydroxyl-proline called LL-AO341 β 1 revealed that specific inhibition of DNA, RNA, protein, lipid, or peptidoglycan synthesis by LL-AO341 β 1 could not be detected.…”
Section: Introductionmentioning
confidence: 99%
“…3 1H1 Peak analysis by NMR spectrum of telomycin antibiotic using chloroform as a solvent Fig. 4 Chemical structure of telomycin as reported by Gurovic et al [15] partial inhibition of the glycoprotein-C dependent binding of the virions, and secondly by inhibition of events that occur after binding the virus to cells [26]. Another effective drug is which, when combined in a low dose with monocaprin, offers an effective treatment for herpes labialis, significantly reducing the time to healing and pain [26,27].…”
Section: Discussionmentioning
confidence: 90%
“…It was discovered in 1958, and the structure was subsequently solved in 1968 [14]. Due to its functional groups found in the structure, it has activity against viral systems such as hemagglutinin-neuraminidase (HN) [15]. The secondary metabolites of S. coeruleorubidus (telomycin: oxaoctaazacyclooctacosine) were studied by investigating its antiviral against influenza virus activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…This natural undecapeptide consists of aspartic acid, serine, threonine, allo -threonine, alanine, glycine, cis - and trans -3-hydroxyproline, β-hydroxyleucine, β-methyltryptophan and α,β-didehydrotryptophan [6]. In recent years, telomycin has also been isolated from the metabolites of Streptomyces canus and Micromonospora schwarzwaldensis [7,8]. Besides, antibiotic LL-AO341β1, an analogue of telomycin, was also obtained as a product of Steptomyces canidus in 1993 [9,10].…”
Section: Introductionmentioning
confidence: 99%